AN ANALYSIS OF WOMAN SPEECH FEATURES USED BY BELLA SWAN IN TWILIGHT BREAKING DAWN II MOVIE - Muhu, Ria Ulfa Handayani; Suhartini, Lelly; Agustina, Sitti (Journal of Teaching of English, 2020)
Many factors influence men and women use of language. One of them is gender refering to the role and responsibilities of men and women created in society. People use different language style while having conversations with different people from different social status in society. This study focuses on woman language features used by Bella Swan in Twilight Breaking Dawn II Movie based on Lakoff study (1975). Design of research conducted was qualitative research. More specifically, the researcher applied discourse analysis to analyse the data. Researcher used Lakoff theory (1975) and Holmes theory (1986) to answer the research questions. Based on data analysis, eight out of ten women speech features from Bella utterances were found in the movie, they were  lexical hedges/fillers, tag questions, rising intonation, ‘empty’ adjectives, intensifiers, emphatic stress, ‘hypercorrect' grammar, and ‘superpolite' forms. Meanwhile, avoidance of strong swear words, andprecise color termswere not found in the movie. The researcher identified three functions of woman speech features used by Bella Swan. They were to express uncertainty, to soften an utterance, and to express feelings or opinion.